Endoscopic Ultrasound-Guided Biliary Access, with Focus on Technique and Practical Tips - Woo Hyun Paik; Do Hyun Park (Korean Society of Gastrointestinal Endoscopy, 2017)
In 1980, endoscopic ultrasound (EUS) was introduced as a diagnostic tool for evaluation of the pancreas. Since the introduction of curvilinear-array echoendoscopy, EUS has been used for a variety of gastrointestinal interventions, including fine needle aspiration, tumor ablation, and pancreatobiliary access. One of the main therapeutic roles of EUS is biliary drainage as an alternative to endoscopic retrograde biliary drainage (ERBD) or percutaneous transhepatic biliary drainage (PTBD). This article summarizes three different methods of EUS-guided biliary access, with focus on technique and practical tips.